Insight into the Effect of Submicellar Concentrations of Sodium Deoxycholate on the Structure, Stability, and Activity of Bovine and Human Serum Albumin An Interesting Comparison between Single and Double Tryptophan Proteins - Mohanty, Subhrajit (Langmuir : the ACS journal of surfaces and colloids, 2024)
The progressive escalation in the applications of bile salts in diverse fields has triggered research on their interaction with various biological macromolecules, especially with proteins. A proper understanding of the interaction process of bile salts, particularly in the lower concentrations range, with the serum albumin seems important since the normal serum concentration of bile salts is approximately in the micromolar range. The current study deals with a comprehensive and comparative analysis of the interaction of submicellar concentrations of sodium deoxycholate (NaDC) with two homologous transport proteins: bovine serum albumin (BSA) and human serum albumin (HSA). HSA and BSA with one and two tryptophans, respectively, provide the opportunity for an interesting comparison of tryptophan fluorescence behavior on interaction with NaDC. The study suggests a sequential interaction of NaDC in three discrete stages with the two proteins. A detailed study using warfarin and ibuprofen as site markers provides information about the sites of interaction, which is further confirmed by inclusive molecular dynamics simulation analysis. Moreover, the comparison of the thermodynamics and stability of the NaDC-serum albumin complexes confirms the stronger interaction of NaDC with BSA as compared to that with HSA. The differential interaction between the bile salt and the two serum albumins is further established from the difference in the extent of decrease in the esterase-like activity assay of the proteins in the presence of NaDC. Therefore, the present study provides important insight into the effect of submicellar concentrations of NaDC on the structure, stability, and activity of the two homologous serum albumins and thus can contribute not only to the general understanding of the complex nature of serum albumin-bile salt interactions but also to the design of more effective pharmaceutical formulations in the field of drug delivery and biomedical research